2021
DOI: 10.3389/pore.2021.612969
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer that Highly Express Both ACE2 and TMPRSS2, Suggesting Severe Symptoms to SARS-CoV-2 Infection

Abstract: The epidemic of the novel, pathogenic SARS-coronavirus 2 (SARS-CoV-2) in the world pose a global health emergency. Cancer has been identified as a risk factor for the novel Coronavirus disease 2019 (COVID-19). The ACE2 and TMPRSS2 have been implicated in SARS-CoV-2 infection for mediating viral entry into the host cell. However, a systematic analysis of aberrant expression of ACE2 and TMPRSS2 was not yet reported in multiple human cancers. Here, we analyzed gene expression of ACE2 and TMPRSS2 across 31 types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, studies concerning the implications of TMPRSS2 expression in patients with CRC remain conflicting. Wang et al showed that TMPRSS2 was highly expressed in CRC which suggests severe symptoms of SARS-CoV-2 Infection ( 27 ). We thus applied multiomics tools to explore the role of TMPRSS2 expression in CRC and evaluated the correlation between TMPRSS2 expression and immunotherapy response to glean new insights into the impact of COVID-19 infection on CRC.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies concerning the implications of TMPRSS2 expression in patients with CRC remain conflicting. Wang et al showed that TMPRSS2 was highly expressed in CRC which suggests severe symptoms of SARS-CoV-2 Infection ( 27 ). We thus applied multiomics tools to explore the role of TMPRSS2 expression in CRC and evaluated the correlation between TMPRSS2 expression and immunotherapy response to glean new insights into the impact of COVID-19 infection on CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese Drug Administration approved 3 proprietary Chinese medicines, including Lianhuaqingwen granules, for the treatment of COVID-19 ( Ni et al, 2020 ). ACE2 and TMPRSS2 proteins mediate SARS-CoV-2 virus invasion into host cells, and among all cancers, only patients with COAD and rectal adenocarcinoma showed upregulated expression of ACE2 and TMPRSS2 proteins in vivo , so patients with COAD and rectal adenocarcinoma may be more susceptible to contracting SARS-CoV-2 ( Hoang et al, 2021 ; Wang and Yang, 2021 ). Furthermore, it was found that cancer patients infected with SARS-CoV-2 virus tend to have a poorer survival prognosis than healthy patients infected with SARS-CoV-2 virus due to the suppression of the systemic immune system caused by the effects of tumor and anti-cancer treatment ( Liang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 expression is also raised in renal cancer and gastrointestinal cancer [52]. It is noteworthy that ACE2 and TMPRSS2 are expressed at high levels on tumor and normal colorectal epithelial tissues and that patients with colorectal cancer and COVID-19 are more likely to have lymphopenia, higher respiratory rate, and high hypersensitive C-reactive protein levels than matched patients with COVID-19 but without cancer [53,54]. Finally, landscape profiling analyses on the expression level of ACE2 in pan-cancers have revealed that the risk for development of SARS-CoV-2 infection was coupled with the expression level of ACE2 [36].…”
Section: Cancermentioning
confidence: 99%